Beneficial Effects of Elderly Tailored Mediterranean Diet on the Proteasomal Proteolysis - Athanasopoulou, Sophia; Chondrogianni, Niki; Santoro, Aurelia; Asimaki, Konstantina; Delitsikou, Vasiliki; Voutetakis, Konstantinos; Fabbri, Cristina; Pietruszka, Barbara; Kaluza, Joanna; Franceschi, Claudio; Gonos, Efstathios S. (Frontiers in Physiology, 2018)
Aging is a multifactorial process characterized by the accumulation of proteins undergoing oxidative modifications, either due to enhanced levels of oxidative stress or due to their decreased clearance; both facts are related to the establishment of chronic inflammatory processes. These processes are directly associated with functional and structural modifications of a key cellular component, namely the proteasome. In this study, levels of oxidized proteins, along with proteasome and immunoproteasome composition and activity on a selected group of 120 elderly volunteers were analyzed before and after the administration of a specific dietary protocol, based on an elderly tailored Mediterranean diet (the “NU-AGE diet”). A significant negative correlation between levels of oxidized/carbonylated proteins and proteasome function was confirmed, both before and after intervention. Furthermore, it was demonstrated that subgroups of non-frail subjects and women receive a greater benefit after the intervention, concerning specifically the proteasome content and activity. These data highlight the putative beneficial effects of Mediterranean diet on the major cellular proteolytic mechanism, the proteasome, in elderly people.